1990
DOI: 10.1007/bf01202428
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of ascorbic acid and erythorbic acid in processed meat by HPLC

Abstract: A simple and efficient HPLC method is described to measure both ascorbic and erythorbic acid separately in processed meat products. The system used consisted of a reversed-phase column, a mobile phase containing an ion-pairing agent and ultraviolet detection. The procedure, which was checked on a variety of samples, was found to give reproducible and reliable results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…When the possibility of a CN column was explored, it was found that this column was not suitable for the simultaneous determination of AA, EA, AA-2G and AA-2␤G (data not shown). Ion-pair RPLC can be used as an alternative method, since measurements of AA and EA in processed meat [8] and measurements of AA and AA-2␤G in rat plasma [17] have been carried out using an ODS column with an ion pair reagent. However, we chose a HILIC column rather than an RPLC column for the following reasons:…”
Section: Choice Of Hilic Modementioning
confidence: 99%
See 1 more Smart Citation
“…When the possibility of a CN column was explored, it was found that this column was not suitable for the simultaneous determination of AA, EA, AA-2G and AA-2␤G (data not shown). Ion-pair RPLC can be used as an alternative method, since measurements of AA and EA in processed meat [8] and measurements of AA and AA-2␤G in rat plasma [17] have been carried out using an ODS column with an ion pair reagent. However, we chose a HILIC column rather than an RPLC column for the following reasons:…”
Section: Choice Of Hilic Modementioning
confidence: 99%
“…However, the antiscorbutic activity of EA is limited and has been reported to be only one-twentieth of that of AA in guinea pigs [7]. Except for high-performance liquid chromatography (HPLC) [8,9] and capillary electrophoresis [10] to measure vitamin C do not distinguish between the two isomers.…”
Section: Introductionmentioning
confidence: 98%
“…No vitamin C values are reported in the literature (Agriculture Handbook No. 8, 1963) because the spectroscopic methods used in the past decades could not differentiate between AA and IAA and they lacked the sensitivity obtained in recently published liquid chromatographic methods (Vanderslice and Higgs, 1990a,b;Schuep and Keck, 1990;Madere, 1992, 1994). Several authors have reported that vitamin C improves pigment and lipid stability in ground beef (Shivas et al, 1984;Mitsumoto et al, 1991) to maintain the fresh appearance of the ground beef.…”
Section: Resultsmentioning
confidence: 96%
“…The biological difference in activity is mainly due to the structural difference in the position of the hydroxyl group at carbon 5 of IAA and AA. Several highly sensitive high-performance liquid chromatography (HPLC) methods have been developed to separate and quantify AA and IAA in processed and other foods Higgs, 1988, 1990a,b;Schuep and Keck, 1990;Madere, 1990, 1992). Recently, we have developed another HPLC method (Behrens and Madere, 1994), which offers several improvements to our previously published method (Behrens and Madere, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Several papers have been published on the liquid chromatographic determination of ascorbic acid in combination with dehydroascorbic acid [13][14][15][16][17][18][19][20][21][22][23][24][25] and/or other compounds [25][26][27][28][29][30][31]. A review article has also been published on analysis of the ascorbic acid and its oxidized form [32].…”
Section: Introductionmentioning
confidence: 99%